2022
DOI: 10.1088/2632-072x/ac7a83
|View full text |Cite
|
Sign up to set email alerts
|

Criticality and network structure drive emergent oscillations in a stochastic whole-brain model

Abstract: Understanding the relation between the structure of brain networks and its functions is a fundamental open question. Simple models of neural activity based on real anatomical networks have proven effective in describing features of whole-brain spontaneous activity when tuned at their critical point. In this work, we show that indeed structural networks are a crucial ingredient in the emergence of synchronized oscillations in a whole-brain stochastic model at criticality. We study such model in the mean-field l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…While the authors of another study simulating Ising dynamics on connectomes 47 hypothesize that structural connectivity alone cannot explain some effects observed in functional correlations of patients after severe brain injuries, no other explanation has been provided in the literature. Our explanation of the anomalous behavior of the cluster-based indicator of criticality, on the other hand, is consistent with the distinction 51 , 52 between well-known structurally-driven percolation phase transitions and dynamic transitions-for which less is known 36 . Reframed in these terms, our results would suggest that in brain strokes there is no change in whatever underlies dynamic transitions, but that there are structural changes that could disorganize the percolation-like transitions.…”
Section: Discussionsupporting
confidence: 86%
“…While the authors of another study simulating Ising dynamics on connectomes 47 hypothesize that structural connectivity alone cannot explain some effects observed in functional correlations of patients after severe brain injuries, no other explanation has been provided in the literature. Our explanation of the anomalous behavior of the cluster-based indicator of criticality, on the other hand, is consistent with the distinction 51 , 52 between well-known structurally-driven percolation phase transitions and dynamic transitions-for which less is known 36 . Reframed in these terms, our results would suggest that in brain strokes there is no change in whatever underlies dynamic transitions, but that there are structural changes that could disorganize the percolation-like transitions.…”
Section: Discussionsupporting
confidence: 86%
“…From a broader perspective, our findings document power law scaling of neural activity during language processing in the newborn brain. This statistical property is a hallmark of critical phenomena, and it has been suggested that criticality in the brain is linked to states of optimal information transmission and storage (49)(50)(51)(52). The newborn brain may thus already be in an optimal state for the efficient processing of speech and language, underpinning human infants' unexpected language learning abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Schwalger et coauthors proposed a system of equations for several interacting populations at the mesoscopic scale, starting from a microscopic model of randomly connected generalized integrateand-fire neuron models for networks varying between 50-2000 neurons [5]. In turn, in [6], it was shown that structural networks are a crucial component of the stochastic brain model on the mesoscopic scale. A metric called multiscale relevance (MSR) was proposed in [7] to capture the dynamic variability of the activity of single neurons across different scales.…”
Section: Introductionmentioning
confidence: 99%